Aptid??o cardiorrespirat??ria, capacidade funcional, for??a muscular, qualidade de vida e n??vel de atividade f??sica di??ria em crian??as e adolescentes asm??ticos - Reimberg, Mariana Mazzuca (2015)
Dyspnea is a symptom of asthmatic patients and may be thecause of decreased physical and functional capacity. The aim of this study was to compare the cardiorespiratory fitness, functional capacity, quality of life (QOL), peripheral muscle strength (FMP) and level of daily physical activity (DPA) of children and adolescents with asthma. Cross-sectional study in patients between 7-18 years old, diagnosed with asthma and their healthy peers. It was performed spirometry, cardiopulmonary exercise testing (CPET), Incremental Shuttle Walk Test (ISWT), FMP of rectus femoris and biceps brachii and number of steps per day (accelerometry). The metabolic and ventilatory demands were measured during CPET and ISWT. The Student t test was used to compare the groups. We evaluated 40 volunteers from asthma group (AG) and 26 from control group (CG), mean age 11 ?? 3 years old and eutrophic. There was no statistically significant difference in the distance of ISWT, the maximal load in CPET and metabolic and ventilatory demand between groups (p>0,05). There was also no difference of FMP between groups. The heart rate at the peak of the tests was above 80%pred in both groups, with no difference between them at SWT AG: 93 ?? 7%pred vs CG: 93 ?? 6%pred and at CPET AG: 83 ?? 9%pred] vs CG: 83?? 10%pred. All volunteers were evaluated as good quality of life, however sedentary. The asthmatic patients do not show any differences in cardiorespiratory fitness, functional capacity, quality of life, FMP number of steps per day compared to control group.